MEMAKSIMALKAN POTENSI MEDIA SOSIAL DALAM STRATEGI PEMASARAN - Miftahudin, Aris Miftahudin; Muhammad Iqbal Fasa (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
Social media has now become an integral part of people's lives. In Indonesia, more than half of the population uses social media in their daily lives. Social media marketing is most commonly used by entrepreneurs because it is easier to use and can directly reach consumers. Therefore, entrepreneurs are required to create creative ideas and new innovations that can attract consumers. The research method used is a descriptive qualitative method, specifically a literature review. The results of the study show that the use of social media can maximize marketing strategies.